The complex pathology of diabetic nephropathy in humans: review - Kriz, Wilhelm; Löwen, Jana; Gröne, Hermann-Josef (Nephrology, dialysis, transplantation, 2023)
This review summarizes the pathomorphological sequences of nephron loss in human diabetic nephropathy (DN). The relevant changes may be derived from two major derangements. First, a failure in the turnover of the glomerular basement membrane (GBM) based on an increased production of GBM components by podocytes and endothelial cells leading to the thickening of the GBM and accumulation of worn-out GBM in the mesangium. This failure may account for the direct pathway to glomerular compaction and sclerosis based on the continuous deposition of undegraded GBM material in the mesangium. Second, an increased leakiness together with an increased propensity of glomerular capillaries to proliferate leads to widespread plasma exudations. Detrimental are those that produce giant insudative spaces within Bowman's capsule, spreading around the entire glomerular circumference and along the glomerulo-tubular junction onto the tubule resulting in tubular obstruction and retroactively to glomerulosclerosis. Tubular atrophy and interstitial fibrosis develop secondarily by transfer of the glomerular damage onto the tubule. Interstitial fibrosis is locally initiated and apparently stimulated by degenerating tubular epithelia. This leads to a focal distribution of interstitial fibrosis and tubular atrophy accompanied by a varying interstitial mononuclear cell infiltration. Spreading of fibrotic areas between intact nephrons, much less to the glomerulus, has not been encountered.